Knowledge-Based Religious Behavior: From Philosophical Critic towards Synergy in Diversity Amidst the Anthropocentrism Era - Sumper Mulia Harahap; Muhammad Ikbal; Marlian Arif Nasution (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
This study is conducted to criticize religious behavior in recent times. This study aims to answer the problem of how to create togetherness by synergy (ukhuwah) mobilizing all components in the context of life in a nation and state. The data of this study were obtained from library sources by applying a library research model with an interdisciplinary approach. The results of the study showed that universal ideas about diversity can be accepted by every intelligent human being. Moreover, there are three main conditions to implement them (universal ideas about diversity). They are; first, Maximum mastery of science and knowledge. Second, Justice reinforcement for human equality. Third, total submission and self-approach to God Almighty. Religion is the most precise medium to describe the true nature of humanity because religion does not only talk about physical things but also beyond human physics. Therefore, a human must understand that togetherness is realized based on humanity, understanding universal values and similar points of diversity, sharpening the function of mind via philosophical practice approach as a method of thinking, mobilizing ukhuwah as the part of net-working the people, and synergize the dimension of heaven and dimension of earth toward intellectual and social piety.